Transforming Rural Economies: The Socioeconomic Impact of Microfinance in Kailali District, Nepal - Bhatta, Dharma Dev (Journal of Durgalaxmi, 2024)
Microfinance has been widely promoted as a strategy for poverty alleviation in developing countries. This mixed-methods study evaluates the socioeconomic impact of microfinance services on the rural poor in Kailali district, Nepal. We surveyed 150 microfinance beneficiaries from three major microfinance institutions and conducted in-depth interviews and focus group discussions. The findings indicate that access to microfinance leads to positive socioeconomic outcomes, including increased income, asset accumulation, improved food security, and better education for children. However, the impact varies across different types of loans, geographic regions, and occupations. The study also reveals challenges such as over-indebtedness and repayment stress among some participants. These findings have important implications for microfinance policy and practice in Nepal and similar contexts.